Hubungan Tingkat Pengetahuan Diare Ibu dengan Kejadian Diare Balita di Wilayah Kerja UPTD Puskesmas Cikidang - Muhamad Gio Juliansyah; Siska Nia Irasanti; Sara Puspita (UNISBA Press, 2023)
Abstract. Diarrhea is a disease that causes an increase in the frequency of bowel movements or a change in the consistency of the stool with high fluid content. Diarrhea is the 2nd cause of death worldwide. The incidence of diarrhea in Indonesia is 16.7%, the highest is in the province of West Java with a total of 364,749 incidents. The purpose of this study was to determine the relationship between the level of maternal prevention knowledge and the incidence of diarrhea in toddlers in the working area of the UPTD Cikidang Health Center. This research is analytic observational with cross sectional design. The sampling method is simple random sampling. The number of samples in the study amounted to 111 people, consisting of 54 (49%) mothers who had diarrhea under five and 57 mothers (51%) who did not have diarrhea. Data obtained from the results of filling out the questionnaire, using the chi-square test analysis. The results showed that most mothers knew what diarrhea was, as many as 76 respondents (67.9%), the remaining 35 respondents (31.5%) had poor knowledge. The results of the analysis showed that there was no significant relationship between knowledge (p=0.69)). Results that were not significant could be influenced by other factors that contributed to the incidence of diarrhea. Abstrak. Diare merupakan penyakit yang menyebabkan peningkatan frekuensi buang air besar atau perubahan konsistensi tinja dengan kadar cairan yang tinggi. Diare menjadi penyebab kematian ke 2 di seluruh dunia. insidensi diare di Indonesia sebanyak 16,7%, yang tertinggi adalah di provinsi Jawa barat dengan jumlah 364.749 insidensi. Tujuan penelitian ini untuk mengetahui hubungan Tingkat pengetahuan pencegahan ibu dengan kejadian diare pada balita di wilayah kerja UPTD Puskesmas Cikidang. Penelitian ini adalah observasional analitik dengan desain cross sectional. Metode pengambilan sampel adalah simple random sampling. Jumlah sampel pada penelitian berjumlah 111 orang, terdiri dari 54 (49%) ibu yang memiliki balita diare dan 57 ibu (51%) yang tidak memiliki balita diare. Data diperoleh dari hasil pengisian kuesioner, dengan menggunakan analisis chi-square test. Hasil menunjukan mayoritas ibu mengetahui tentang apa itu diare sebanyak 76 responden (67,9%) sisanya sebanyak 35 responden (31.5%) memiliki pengetahuan yang kurang baik. Hasil analisis menunjukkan bahwa tidak terdapat hubungan yang bermakna antara pengetahuan (p=0.69). Hasil yang tidak bermakna dapat dipengaruhi oleh faktor lain yang berkontribusi terhadap kejadian diare.